WACANA KRITIS CELAAN FISIK DALAM FILM IMPERFECT: ANALISIS STRUKTUR TEKS, KOGNISI SOSIAL, DAN KONTEKS SOSIAL - Siti Aisyah; I Wayan Letreng; Sri Yanuarsih (Jurnal Bastra (Bahasa dan Sastra), 2025)
This study aims to analyze the discourse of physical abuse against women in Ernest Prakasa's film This study aims to examine the critical discourse of physical abuse in the film Imperfect using Teun A. van Dijk's Critical Discourse Analysis (CDA) approach. The study focuses on three main dimensions: text structure, social cognition, and social context. The film Imperfect was chosen because it represents social issues such as body shaming, pressures of beauty standards, and the physical marginalization experienced by female characters. The research method used is descriptive qualitative, with data collection techniques consisting of observation and documentation of the film's dialogues. The results show that: (1) Structurally, the discourse of physical abuse in the film is constructed through word choice, narrative structure, and the use of verbal expressions that depict physical stereotypes. (2) Social cognition in the film shows how social actors understand and reproduce the ideology of beauty rooted in society. (3) The social context shows that the discourse of physical abuse arises due to the influence of popular culture, the beauty industry, and the dominant patriarchal system. This study concludes that language in the film Imperfect is not only a means of communication, but also a means of reproducing ideology and power over women's bodies.